Development of a modern control system analysis package using visual basic programming - Rahmat, Mohd. Fua'ad; Lee, Shu Khan (Faculty of Electrical Engineering, UTM, 2007)

(untitled)
This paper introduces a Computer Aided Control System Design (CACSD) program that furnishes a background necessary for studying modern control theory. The program focuses on state-space analysis which performs conversion of a system from state-space representation to transfer function and via versa. Besides, system transformation on different state coordinates, time domain solution, controller design, observer design and steady state error evaluation with interactive graph response are also being emphasized in this program.